2021
DOI: 10.32802/asmscj.2021.580
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of Zinc Layered Hydroxide Intercalated with 2-Methyl-4- Chlorophenoxyacetic Acid and its Controlled Release Application

Abstract: 2-methyl-4-chlorophenoxyacetic acid (MCPA) is herbicide in group of phenoxyherbicides. It has been widely used in agriculture industry to control the weeds population especially thistle and dock. The toxicity of MCPA may impact the environment and harmful for living organisms especially human and aquatic life. This research aimed to intercalate MCPA herbicide with zinc layered hydroxide (ZLH) to form a composites (ZMCPA) and its controlled release properties. In this study, ZMCPA was prepared as an advanced de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…There are various synthesis methods have been used to synthesize ZLH nanocomposite, which an ionexchange method [26][27][28], co-precipitation method [4, [18][19][20], hydrothermal precipitation methods [12,[29][30], and direct reaction method [31][32][33]. Above all, the direct reaction method is often chosen in preparing ZLH nanocomposites because various anions can be directly intercalated alternately between the hydroxylated sheets and increase the quantity of the synthesized material [26,[31][32][33][34]. The ion exchange process is not involved in this method.…”
Section: ■ Synthesis Methods Of Zinc Layered Hydroxidementioning
confidence: 99%
See 1 more Smart Citation
“…There are various synthesis methods have been used to synthesize ZLH nanocomposite, which an ionexchange method [26][27][28], co-precipitation method [4, [18][19][20], hydrothermal precipitation methods [12,[29][30], and direct reaction method [31][32][33]. Above all, the direct reaction method is often chosen in preparing ZLH nanocomposites because various anions can be directly intercalated alternately between the hydroxylated sheets and increase the quantity of the synthesized material [26,[31][32][33][34]. The ion exchange process is not involved in this method.…”
Section: ■ Synthesis Methods Of Zinc Layered Hydroxidementioning
confidence: 99%
“…Special attention has also been focused on controlled-release formulations of pesticides using layered materials in agriculture. There are many new nanocomposites involving pesticides that have been intercalated into interlayer of ZLH such as cetyltrimethylammonium bromide [125], chloroacetic acid [33], valeric acid [47], propoxur [41], isoprocarb [126], thiacloprid [28], 2-methyl-4-chlorophenoxyacetic acid [34], 2-(2,4-dichlorophenoxy) butyric acid [55], and 4-chlorophenoxyacetic acid [127]. The successful intercalation process of pesticides into the interlayer of ZLH was due to positively charged ZLH layers that promote the attraction force between the guest anion pesticides and the host.…”
Section: ■ Controlled Release Formulation In Agriculturementioning
confidence: 99%
“…The intercalated pesticide has higher thermal stability. The release rates and equilibrium release amounts of the pesticide were closely dependent on micelles types and release media [69] Other pesticides that were intercalated into Zn-LH are 3-(4-methoxyphenyl) propionic [63], imidacloprid [64], 4-(2,4-dichlorophenoxy) butyrate and 2-(3-chlorophenoxy) propionate [65] and 2-methyl-4-chlorophenoxyacetic [66]. They were synthesized due to their superior qualities compared with their counterparts.…”
Section: -Glycidyloxypropyl) Trimethoxysilanementioning
confidence: 99%
“…Other pesticides that were intercalated into Zn-LH are 3-(4-methoxyphenyl) propionic [ 63 ], imidacloprid [ 64 ], 4-(2,4-dichlorophenoxy) butyrate and 2-(3-chlorophenoxy) propionate [ 65 ] and 2-methyl-4- chlorophenoxyacetic [ 66 ]. They were synthesized due to their superior qualities compared with their counterparts.…”
Section: Nanopesticides Synthesized Using 2d Inorganic Layered Hydroxides Hostsmentioning
confidence: 99%
“…Subsequently, hydrothermal treatment was employed to increase the product's crystallinity. To clarify, there are few studies on intercalating MCPA into ZLH that have been employed [25,26], but there haven't been any published studies investigating the effect of protein and amino acid content of plant samples treated by this nanoherbicide yet. Due to this reason, in this present study, the protein and amino acid composition in leaves of bean sprout samples was reported following the application of herbicide with aimed to broaden the limited scientific knowledge by supporting the impact of nanoherbicides on plant gene expression.…”
Section: Introductionmentioning
confidence: 99%